Influential Article Review - Examining Interactions in Collaborative Innovation Activities - Ballard, Faye; Brady, Eric; Cobb, Frances (Journal of Strategic Innovation and Sustainability, 2019)
This paper examines innovation.. We present insights from a highly influential paper. Here are the highlights from this paper: Collaborations in innovation work between competitors have become a common practice in the information and communication technology sector (ICT), and substantial investments are made in such collaborations. Significant rationales for these collaborations include the high expectations placed on rapid and front-edge technology development and business exploitation. However, there is often a failure to reach the expected outcomes of such collaborations. This may be explained not only by the challenges and obstacles in technology development but also by the social relations within the collaborations. The purpose of this study is to explore the role of social exchange in the outcomes of early-stage innovation collaborations. More specifically, we explore the social facilitators of exchange and how such facilitators may influence collaboration outcomes. Social exchange theory is used for this purpose. This longitudinal study is based on a 3-year collaboration project for innovation using qualitative methods (29 interviews, observations of 7 project meetings). Three phases of social exchange in the collaboration are empirically identified: the dating phase, brainstorming phase, and decision phase. Three social facilitators of social exchange within these phases are conceptualized: trust, commitment, and congruence. Further, direct contacts are conceptualized as a social accelerator fueling these social facilitators. This study advances understanding of social facilitators in social exchange and their significance regarding success/failure outcomes. Risks of lock-in situations in collaborations for innovation are outlined in a knowledge exchange paradox. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.